HUBUNGAN GAYA KEPEMIMPINAN SELLING DENGAN KEPUASAN KERJA KARYAWAN BAGIAN FRONTLINER PADA METRO PLAZA PASAR SWALAYAN PEKANBARU - Kuncoro, Budi; Sutrisna, Endang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The aim of this research is to know the leadership style and work satisfaction of frontliner employee at Metro Plaza Pasar Swalayan Pekanbaru.This research takes place in Metro Plaza which located at Harapan Raya street no 201 Pekanbaru. This is qualitative research with case study data; investigate the correlation between selling leadership style and work satisfaction of frontliner employee at Metro Plaza pasar Swalayan Pekanbaru, population of this research is the frontliner employee in the and of year 2012, they are 80 persons. Sample taken is the whole population by using sensus technique. Analyzing the data using correlation rank spearman formula.The finding of the research shows that tenponses of respondent about work satisfaction in category agree, where some frontliner employees feel satisfy with the leadership that applied at Metro Plaza Pasar Swalayan Pekanbaru, responses of the respondent about selling leadership style in category good, for most of employess agree with leadership style applied by the company.The result of correlation between selling leadership style and work satisfaction of frontliner employee using rank spearman formula shows that there are great and positive correlation.Keywords: Leadership, Selling Leadership style, work satisfaction